PP4 Journey towards excellence in orienteering: analysis of elite athletes' life stories. (21st October 2014) - Celestino, T; Leitão, J; Sarmento, H; Marques, A; Pereira, A
Abstract : The search for perfection and being excellent is a challenge that has been following in every area of human realisation. This development process has its genesis in childhood and is a consequence of a long-term investment. Considering this, it is necessary to understand excellence as a multidimensional and evolving process. Therefore, this study aimed at characterising the development path of a group of excellent athletes, in order to identify the factors which influence and determine the development of excellence in orienteering. The study focused on a group of 5 elite orienteering athletes, positioned among the top 10 in the IOF 2013 world ranking. Data was collected via semi-structured interviews and the study was developed using life stories methodology. Later the data was analysed using content analysis. Results have shown that being excellent implies developing personal excellence, in which the performance excellence is complemented by the development of a series of actions of personal growth. Hence, this group of athletes shows a need to have a set of characteristics such as professionalism and commitment towards the development of excellence. It was identified that sport diversification is the base principle for all sport development processes with excellence and it is organised in three fundamental steps: initiation, which is characterised by a investment in free and deliberate game; development, denoting a commitment to orienteering and structured training; improvement, highlighting the diversification of the locations to practice as core aspects. These athletes have attributes special importance to the context on which this process is developed, naming family, friends influence, as well as sociocultural dynamic of a country or region. Lastly, a set of determinant factors of positive affective-emotional nature were identified, were feelings of wellbeing and passion for the sport act as influence elements towards the development of excellence.